Hypoxia exacerbates cardiomyocyte injury via upregulation of Wnt3a and inhibition of Sirt3. (December 2020) - Li, Yanming; Du, Luping; Cheng, Siya; Guo, Jingjing; Zhu, Shengnan; Wang, Yunlong; Gao, Hai
Abstract: Ischemic injury is a major cause of several cardiovascular diseases, such as myocardial infarction, cardiac hypertrophy, and ventricular remodeling. Using an in vitro hypoxia model to mimic ischemia, we found that hypoxia stimulated Wnt3a expression. A mechanistic study showed that hypoxia-inducible factor 1α (HIF-1α) was directly recruited to the Wnt3a promoter. Wnt3a overexpression significantly decreased cell viability, promoted the generation of apoptotic cells, and enhanced hypoxia-induced injury in neonatal rat cardiomyocytes. This was partially through the upregulation of Caspase-3 mRNA levels and cleaved PARP-1 protein levels. In addition, we observed that Wnt3a exacerbated hypoxia-induced mitochondrial dysfunction and cytosolic release of cytochrome C . Furthermore, we found that Sirt3, a mitochondrial NAD + -dependent deacetylase that modulates mitochondrial metabolism and homeostasis, was negatively regulated by Wnt3a. Conversely, Sirt3 overexpression repressed Wnt3a expression and ameliorated the hypoxia-induced mitochondrial dysfunction. Overall, our findings suggest that the hypoxia–Wnt3a–Sirt3 regulatory axis might be a potential target for cell protection in cardiac ischemia and hypoxia.